(untitled) (Damascus University Journal for the basic sciences, 2022)
Lead pencil electrode was modified by scanning voltammetry in a mixture of nitric acid and lithium perchlorate electrolyte. The electrode was used as a sensor to determine oleuropein in extract of dried olive leaves extract. oleuropein is the highest available component among of the polyphenols in the olive leave extract. ( DPV) differential striping voltammetry technique was utilized with EIS to characterize the modified electrode. A noticeable enhancement of electrode. Electrochemical reactivity was noticed an oxidation maximum appeared at 0.5V as a result of Ole oxidation with linear change of its current light versus Ole concentration.(range: 5.4*10-4M ̶ 8.8*10-5 M) with Dl=5.4*10-5M at accumulation time =2 min and the value of the R2=0.989 the described electrode has a lower residual current, no was than 10µA. All effective parameters was studied (e.g: v, PH, t)